The Effect of Awareness, Trust and Brand Image on Intention to Use Sharia Insurance Products with Knowledge as a Moderating Variable in Medan Belawan - Indah Ussania; Isnaini Harahap; Juliana Nasution (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The purpose of this study was to determine the effect of awareness, trust and brand image on the intention to use Islamic insurance products with knowledge as a moderating variable in Medan Belawan. The population in this study were Islamic insurance customers in Medan Belawan. The sampling technique used purposive sampling with a total of 100 respondents. The data analysis technique applied in this research is quantitative analysis by applying Moderated Regression Analysis (MRA). The results showed that: (1) awareness has a significant influence on increasing the intention of Sharia insurance products in Medan Belawan. The value of t count> t table or -2.600 < 1.660881 and obtained a significance value < 0.05 alpha level or 0.011 < 0.05.  (2) trust has a significant influence on increasing the intention of respondents of Sharia insurance products in Medan Belawan. The value of the t value> t table or 2, 329> 1.660881 and obtained a significance value < alpha level 0.05 or 0.022 < 0.05. Thus, the hypothesis can be accepted. (3) brand image has a significant influence on increasing the intention of Sharia insurance products in Medan Belawan. The value of t value> t table or or 2, 766> 1.660881 and obtained a significance value < alpha level 0.05 or 0.007 < 0.05, so the hypothesis is accepted. (4) knowledge is able to moderate the influence of awareness, trust, and brand image variables on the intention of Sharia insurance products in Medan Belawan.